Outcomes of Feeding Problems in Advanced Dementia in a Nursing Home Population - Hanson, Laura C. (J Am Geriatr Soc, 2013)
OBJECTIVES: Weight loss is common in advanced dementia, but regulators and clinicians are uncertain how often it is treatable. Study objectives were to describe: 1) quality of care for feeding problems in advanced dementia, and 2) probability and predictors of weight loss and mortality. DESIGN: Prospective cohort SETTING: 24 nursing homes PARTICIPANTS: 256 residents with advanced dementia and feeding problems, and family surrogates MEASUREMENTS: Family reported on quality of feeding care at enrollment and 3 months. Chart reviews at enrollment, 3, 6 and 9 months provided data on feeding problems, treatments, weight loss of >5% in 30 days or >10% in 6 months, and mortality. Organizational variables were obtained from administrator surveys and publically reported data. RESULTS: Residents with advanced dementia and feeding problems had an average age of 85; 80% had chewing and swallowing problems, 11% weight loss and 48% poor intake. Family reported feeding assistance of moderate quality; 23% felt the resident received less assistance than needed. Mortality risk was significant; 8% died within 3 months, 17% within 6 months and 27% within 9 months. Residents with advanced dementia and stable weight had a 5.4% rate of significant weight loss and a 2.1% risk of death over 3 months. Residents with advanced dementia and weight loss had a 38.9% chance of stabilizing weight over the next 3 months, but also had a 19.2% chance of dying. Weight loss was the only independent predictor of death. CONCLUSION: Weight loss is a predictor of death in advanced dementia. Treatments can often stabilize weight, but weight loss should be used to trigger discussion of goals of care and treatment options.